Diversité Floristique Et Variation Altitudinale De La Structure Des Formations A Gnidia Glauca (Fresen) Gilg. Dans Les Forêts Communautaires De KilumIjim (Nord-Ouest Cameroun) - M. C., Momo Solefack; Y. B., Kamga; V. F., Nguetsop; B., Tiokeng; M. L., Avana - Tientcheu; V.A., Kemeuze (European Scientific Journal, ESJ, 2017)
In order to find strategies for sustainable management of resources, a study was carried out on the analysis and management of stands of Gnidia glauca in the Kilum-Ijim region (North-West Cameroon). All individuals were identified and counted in 33 plots of 40mx40m established between 1963 and 2785 m altitude in these Gnidia glauca formations. The height and diameter of each individual were measured. A quadrat of 1m² was established around the mature trees to evaluate the regeneration. ANOVA was used to compare the average density of the species in various plots and the DUNCAN test at the 5% significance level (SPSS software version 17.0) was used to separate these means. It emerges from this study that the Thymelaeaceae (G. glauca) family is mainly represented. The Asteraceae, Rubiaceae, Poaceae and Fabaceae are the most diverse families in these formations. The distribution of individuals of G. glauca in diameter classes shows a decreasing pattern. The low density of G. glauca is observed at low altitudes (166.66 stems / hectare), and the high density is between 2350 and 2450 m (778.18 stems / ha). The average standing densities of G. glauca varies between 64.58 and 459.37 stems per hectare; these values indicate a good regeneration of this species in the site. G. glauca can therefore be rationally exploited in a sustainable way for the well-being of the surrounding human populations.